TINJAUAN YURIDIS TUGAS DAN KEWENANGAN JAKSA DEMI TERCAPAINYA NILAI-NILAI KEADILAN - Djunaedi Djunaedi (UNISSULA, 2014)
The dynamics of the law enforcement paradigm, of course, will have consequences on the institution, organization, structure, and position of law enforcement officers, including in this case the Attorney institution. Prosecutors role in achieving a goal of the criminal justice system, it would require continuous efforts to increase the ability of the Public Prosecutor in tackling criminal acts in the community, including the ability to prevent and deal with a crime that happened. Prosecutors also must be able to engage fully in the development process, among others, helped create the conditions and infrastructure to support and secure the implementation of development to realize a just and prosperous society based on Pancasila and the duty tocontribute to maintain and uphold the authority of the government and the state and to protect the interests of the people through law enforcement. Code Criminal Procedure provides that the position of attorney as prosecutor as authorized institutions. In a position as a public prosecutor apparatus, the Criminal Procedure Code asserts that the prosecution authority to make theindictment without the intervention of other agencies, the public prosecutor and the perfect stand alone in making the indictment.